Birth Size and Brain Function 75 Years Later - Muller, Majon (American Academy of Pediatrics, 2014)
BACKGROUND: There are several lines of evidence pointing to fetal and other early origins of diseases of the aging brain, but there are no data directly addressing the hypotheses in an older population. We investigated the association of fetal size to late-age measures of brain structure and function in a large cohort of older men and women and explored the modifying effect of education on these associations. METHODS: Within the AGES (Age Gene/Environment Susceptibility)-Reykjavik population-based cohort (born between 1907 and 1935), archived birth records were abstracted for 1254 men and women who ∼75 years later underwent an examination that included brain MRI and extensive cognitive assessment. RESULTS: Adjustment for intracranial volume, demographic and medical history characteristics, and lower Ponderal index at birth (per kg/m(3)), an indicator of third-trimester fetal wasting, was significantly associated with smaller volumes of total brain and white matter; βs (95% confidence intervals) were −1.0 (−1.9 to −0.0) and −0.5 (−1.0 to −0.0) mL. Furthermore, lower Ponderal index was associated with slower processing speed and reduced executive functioning but only in those with low education (β [95% confidence interval]: −0.136 [−0.235 to −0.036] and −0.077 [−0.153 to −0.001]). CONCLUSIONS: This first study of its kind provides clinical measures suggesting that smaller birth size, as an indicator of a suboptimal intrauterine environment, is associated with late-life alterations in brain tissue volume and function. In addition, it shows that the effects of a suboptimal intrauterine environment on late-life cognitive function were present only in those with lower educational levels.